Implementasi Program Keluarga Harapan di Kecamatan Tigaraksa Kabupaten Tangerang, Banten - Meidiana Meidiana; Tirton Nefianto; Ahmad Hidayat Sutawidjaya; Yahya Rachmana Hidayat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the implementation of the Family Hope Program (Program Keluarga Harapan/PKH) in Tigaraksa District, Tangerang Regency, and to identify the supporting and inhibiting factors affecting its implementation. This study employed a descriptive qualitative approach using a case study method. The research informants consisted of the PKH Coordinator of Tangerang Regency, PKH facilitators, representatives from the Social Affairs Office, village operators, and Beneficiary Families (Keluarga Penerima Manfaat/KPM). Data were collected through interviews, observations, and documentation. Data were analyzed using the Miles, Huberman, and Saldaña (2014) model, guided by Edwards III's policy implementation theory, which comprises communication, resources, disposition, and bureaucratic structure. The findings indicate that the implementation of the Family Hope Program in Tigaraksa District was consistent with the communication, disposition, and bureaucratic structure dimensions of Edwards III's policy implementation theory. This was evidenced by the regular implementation of socialization activities and Family Development Sessions (P2K2), the commitment of PKH facilitators in carrying out their responsibilities, and the existence of well-established coordination mechanisms and implementation guidelines. However, the resource dimension has not yet been optimal due to the limited number of facilitators compared to the number of beneficiary families, delays in updating beneficiary data, and persistent public misunderstandings regarding the eligibility criteria for receiving assistance. This study contributes by providing recommendations to strengthen inter-agency coordination, optimize the number of PKH facilitators, and accelerate beneficiary data updating in order to improve the effectiveness of the Family Hope Program implementation.